Socio-economic gradients in maternal and child health-seeking behaviours in egypt: systematic literature review and evidence synthesis. - Lenka Benova; Oona M R Campbell; George B Ploubidis (PLoS ONE)
Background Health-seeking behaviour lies on the direct pathway between socio-economic position (SEP) and health outcomes. The objective of this systematic review is to identify and synthesise evidence of socio-economic gradients in health-seeking behaviours related to maternal and child health in Egypt. Methods Four databases (Medline, Embase, Global Health and Web of Science) were searched in September 2013 for material published in English from 1992 to 2013 for a combination of terms describing health-seeking behaviours, indicators of socio-economic position and geographical limitation to Egypt. Findings of studies were described and synthesised in a narrative format as meta-analysis was not possible. Findings Among the 786 references identified, 10 articles met the inclusion criteria. Six studies examined maternal and five studies child health-seeking behaviours (one study examined both). For maternal health, three dimensions of health-seeking behaviour (receipt of any care, type of care and intensity of care) were covered by studies of ante-natal and one dimension (type of care) by analyses of delivery care. For child health, two dimensions of preventive care (coverage of and intensity of immunisation) and three dimensions of curative care (receipt of any care, type and cost of care) were analysed. Conclusions Based on two studies of time trends in nationally-representative surveys, socio-economic inequalities in seeking care for basic preventive and curative interventions in maternal and child health appear to have narrowed. Limited evidence of gradients in intensity of maternal preventive and provider selection in child curative care showed that inequalities may have widened. In studies of more geographically and socially homogeneous samples, fewer gradients were identified. Current body of evidence contains numerous limitations and gaps and is insufficient to draw a conclusive summary of such gradients. Improved understanding of SEP gradients is crucial in designing and prioritising interventions to equitably improve maternal and child health outcomes.